Fostering argumentation skills through project of STEM-Engineering Design process - Wisutama, Remanda Arya; Sulaeman, Nurul Fitriyah; Putra, Pramudya Dwi Aristya (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2024)
This study aims to explore students' ability to form argumentation patterns based on aspects of Toulmin's Argument Pattern (TAP) in Science, Technology, Engineering and Mathematics (STEM)-based learning. Data collection was carried out through STEM-based worksheet which has 12 argumentation items that are in accordance with the Engineering Design Process (EDP) stages. The data was then analyzed qualitatively. This research was conducted at one of the junior high schools in Samarinda City in the even semester of the 2022/2023 academic year. The population in this study were all students of grade VII totaling 9 classes with a sample of grade VII-F consisting of 32 students. The results showed that the students' argumentation patterns consisted of several patterns, namely, Claim & Data (C-D); Claims, Data, & Warrants (C-D-W); Claims, Data, Warrants, & Backing (C-D-W-B); Claim, Data, Warrant, Backing, and Rebuttal (C-D-W-B-R) with the C-D pattern is the most common argumentation pattern. Students still need to be facilitated with learning that can guide students in forming more complex arguments so that an argumentation pattern is formed that includes warrant, backing, and rebuttal aspects.